HAKIKAT PERANG DALAM ISLAM (STUDI LIVING HADIS QITᾹL) - Andi Rafida (As-Syifa: Journal of Islamic Studies and History, 2022)
Abstract This research attempts to study the hadith of war narrated by Imam Bukhāri. The results of this study indicate that war has two meanings, namely; physical and non-physical war. Physical war is divided into two, namely; War/ Jihad Mubada'ah and War/ Jihad Dafa'. Mubada'ah war is not justified in Islam because all humans currently live as brothers and sisters as fellow human beings. There are no Muslim or infidel labels in matters of muamalah / social interaction. As for war that aims to defend against enemy attacks, it is permissible to maintain self-dignity and religion. The humans allowed to fight are the infidels who attacked Islam. As well as wars that are allowed are wars that aim to survive and defend themselves when attacked by the enemy. Abstrak Penelitian ini berusaha untuk mengkaji hadis perang yang diriwayatkan oleh Imam Bukhāri. Hasil penelitian ini menunjukkan bahwa perang memiliki dua arti, yaitu; perang fisik dan non fisik. Perang fisik terbagi menjadi dua yaitu; Perang/ Jihad Mubada’ah dan Perang/ Jihad Dafa’. Perang Mubada’ah tidak dibenarkan dalam islam karena seluruh manusia saat ini hidup bersaudara sebagai sesame manusia. Tidak ada label muslim maupun kafir dalam urusan muamalah / interaksi sosial. Adapun perang yang bertujuan untuk bertahan dari serangan musuh, diperbolehkan untuk menjaga martabat diri maupun agama. Manusia yang diizinkan untuk diperangi adalah orang kafir yang menyerang islam. Serta peperangan yang diizinkan adalah peperangan yang bertujuan untuk bertahan dan membela diri saat diserang oleh musuh.